2014
DOI: 10.1002/mop.28349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an ordinary adhesive material on radiation characteristics of a dielectric resonator antenna

Abstract: This article reports the impact of using an ordinary adhesive material to bond a dielectric resonator antenna (DRA) to the ground plane to predict the potential variations in resonant frequency and impedance bandwidth of DRA. A set of aperture fed and monopole fed cylindrical DRAs have been analyzed at resonant frequencies of 2.4 and 8.9 GHz. For DRAs resonating at 2.4 GHz, an upward resonance frequency shift of 6.2% along with increase of 1.4 to 2% in impedance bandwidth have been observed. However, a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…So that, observe in Fig. 7 that, by considering the air gap thickness of To fix the dielectric layers onto each other and also the bottom layer on the ground plane, a commercially available adhesive material with the permittivity of 2.2 − j0.022 is used [33]. As shown in Fig.…”
Section: Measured Resultsmentioning
confidence: 99%
“…So that, observe in Fig. 7 that, by considering the air gap thickness of To fix the dielectric layers onto each other and also the bottom layer on the ground plane, a commercially available adhesive material with the permittivity of 2.2 − j0.022 is used [33]. As shown in Fig.…”
Section: Measured Resultsmentioning
confidence: 99%
“…Slight difference is presented in experimental and simulated | S 11 | because of the effect of glue, which is applied to fix the ceramic material over substrate . The effect of adhesive material is more at high frequency as compare to low frequency because loss tangent of adhesive is largely affected by frequency . From Figure B, it is confirmed that the mutual coupling is lower than −20 dB among the different ports.…”
Section: Experimental Investigationmentioning
confidence: 92%
“…In lower microwave band, DRAs are commonly bonded to their substrates, ground plane, or feeding devices manually with nonconductive glue and soldering [18], [19]. RF conductive tapes are sometimes applied on sidewalls of DRAs to facilitate feeding and soldering [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, when frequency increases, they often cause noticeable problems. For glue, unwanted unevenness, malposition, and air gaps change the designed resonant frequency and bandwidth of DRAs [11], [19]. Drilling and soldering require extra precision, and tapes are not suitable for tiny objects.…”
Section: Literature Reviewmentioning
confidence: 99%